2004
DOI: 10.1021/ja0487933
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Magnets of Ferrous Cubes:  Structurally Controlled Magnetic Anisotropy

Abstract: Tetranuclear Fe(II) cubic complexes were synthesized with Schiff base ligands bridging the Fe(II) centers. X-ray structural analyses of six ferrous cubes, [Fe4(sap)4(MeOH)4].2H2O (1), [Fe4(5-Br-sap)4(MeOH)4] (2), [Fe4(3-MeO-sap)4(MeOH)4].2MeOH (3), [Fe4(sae)4(MeOH)4] (4), [Fe4(5-Br-sae)4(MeOH)4].MeOH (5), and [Fe4(3,5-Cl2-sae)4(MeOH)4] (6) (R-sap and R-sae were prepared by condensation of salicylaldehyde derivatives with aminopropyl alcohol and aminoethyl alcohol, respectively) were performed, and their magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
141
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(146 citation statements)
references
References 53 publications
4
141
1
Order By: Relevance
“…Detailed magnetic studies on 1-3 have shown that pseudohalide substitution in 1 has a marked effect on the magnetic properties of complexes 2 and 3, which behave as single-molecule magnets. This family of SMMs represents the second example of an iron(II) SMM family, besides the cubane complexes [Fe 4 (L) 4 A C H T U N G T R E N N U N G (MeOH) 4 ] (L= sae 2À , the dianion of 2-salicylideneamino-1-ethanol, [16] and L = 5-Br-sae or 3,5-Cl 2 -sae, [17] the respective bromo and chloro derivatives thereof), while we have recently reported [Fe 2 A C H T U N G T R E N N U N G (NCO) 3 (acpypentO)] as another Fe II SMM. [18] Results and Discussion…”
Section: A C H T U N G T R E N N U N G (H 2 O)mentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed magnetic studies on 1-3 have shown that pseudohalide substitution in 1 has a marked effect on the magnetic properties of complexes 2 and 3, which behave as single-molecule magnets. This family of SMMs represents the second example of an iron(II) SMM family, besides the cubane complexes [Fe 4 (L) 4 A C H T U N G T R E N N U N G (MeOH) 4 ] (L= sae 2À , the dianion of 2-salicylideneamino-1-ethanol, [16] and L = 5-Br-sae or 3,5-Cl 2 -sae, [17] the respective bromo and chloro derivatives thereof), while we have recently reported [Fe 2 A C H T U N G T R E N N U N G (NCO) 3 (acpypentO)] as another Fe II SMM. [18] Results and Discussion…”
Section: A C H T U N G T R E N N U N G (H 2 O)mentioning
confidence: 99%
“…[16,17] However, no Mçssbauer spectra are available for these. Their preexponential factors were found to be~10 À9 s, with energy barriers of 26-30 K. With these values, we would expect relaxation effects in the Mçssbauer spectra to emerge in the range 10-15 K. Two other similar alkoxo-bridged ferrous cubes have been reported.…”
Section: Complexmentioning
confidence: 99%
“…After the discovery of the first single-molecule magnet, cluster compound Mn 12 O 12 (O 2 CMe) 16 (H 2 O) 4 [31], efforts to increase the spin relaxation barrier primarily involved research aimed at synthesizing larger metal clusters with higher values of S, typically featuring oxo bridging ligands between metal centers [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. Here, the magnetic interactions between the metal centers occur via superexchange coupling through the diamagnetic oxido unit, and these interactions can indeed reach appreciable magnitudes for such one-atom bridging ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Since the discovering of the first Mn 12 SMM in 1993, [8] many transition-metal-containing (such as Mn, Fe, Ni, V, and d-f) SMMs were obtained and studied deeply. [9][10][11][12][13][14][15] The study proves energy barrier of the SMMs are related to high spin ground state (S) and significant magnetic anisotropy (D). To get SMMs with high energy barrier, S and D need be increased, but Ruiz discloses the S and D can't increase simultaneously.…”
Section: Introductionmentioning
confidence: 98%